A nanoLDH catalyst with high CO2 adsorption capability for photo-catalytic reduction. Issue 20 (14th May 2018) - Tokudome, Yasuaki; Fukui, Megu; Iguchi, Shoji; Hasegawa, Yudai; Teramura, Kentaro; Tanaka, Tsunehiro; Takemoto, Masanori; Katsura, Reo; Takahashi, Masahide
Abstract : Nanohydroxides with metastable surfaces were found to exhibit high photocatalytic activities toward CO2 reduction. Abstract : A benign catalyst with a considerable activity towards CO2 reduction is in demand to explore green processes. Layered double hydroxides (LDHs) are a promising candidate material for this purpose, because they exhibit a high catalytic activity even in aqueous solvents and are free from poisoning by water molecules. Herein, we demonstrate that NiAl LDH nanocrystals (∼20 nm) exhibit a remarkably high photocatalytic activity toward CO2 reduction in aqueous media, thanks to their capability of adsorbing CO2 at high concentration. The present LDH photocatalyst with a high catalytic activity was obtained through a nanocrystallization induced by a homogeneous and rapid pH increase from an aqueous solution of concentrated metal salts. The rate of photocatalytic CO2 reduction over the nanoLDH catalyst (50 μmol h −1 ) is 7 times higher than that over a highly-crystalline standard LDH catalyst (7.2 μmol h −1 ) prepared through a conventional method. Systematic investigation revealed that the excellent catalytic properties of the present nanoLDH originate from its high affinity towards CO2 introduced as the gaseous state. This specific nature of the surface could be related to the metastable surface which was quenched by rapid hydroxide formation from concentrated solution of metals salts. The nanoLDH catalysts demonstrated here can be synthesized in a simple one-pot reaction in an aqueous solvent at a mild temperature. Further exploration of the material design by complexation with co-catalysts would give rise to catalysts for artificial photosynthesis based on nanoLDH materials.